Biomechanics of technique selection in women`s artistic gymnastics: From theory to practice - Manning, M.; Irwin, G.; Kerwin, D. G.; Gittoes, M. J. R. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This research aimed to determine effective technique selection for the female longswing through four themes: contemporary trend (T1), biomechanical conceptual (T2), musculoskeletal (T3) and energetic (T4) approaches. 3D video data at two elite competitions provided high ecologically validity. T1 identified the straddle Tkachev as the ideal vehicle with three distinct preparatory techniques (arch, pike, straddle) preceding it. Significant joint kinematic differences were not replicated in release parameters (T2) although joint kinetics highlighted greater physical demands in the pike (T3), with an energetics effectiveness score highlighting the arch as a technique promoting skill development (T4). Increasing knowledge and understanding allows coaches to optimise technique selection.